ID 266 – Motor unit number estimation in acute inflammatory demyelinating polyneuropathy. Issue 3 (March 2016) - Vaeggemose, M.; Fuglsang-Frederiksen, A.; Andersen, H.; Isak, B.; Harbo, T.; Tankisi, H.
Abstract : Objective: To evaluate motor unit loss using Multiple Point Stimulation (MPS)-Motor Unit Number Estimation (MUNE) and motor unit number index (MUNIX) in patients with Acute Inflammatory Demyelinating Polyneuropathy (AIDP). Methods: MPS-MUNE and MUNIX on abductor pollicis brevis (APB) were done at week-1 and week-4 of symptom onset in 10 AIDP patients (mean age: 50.10) and in 22 healthy controls (mean age: 49.82). Motor unit size was calculated as surface-Motor-Unit-Potential (sMUP) and Motor-unit-size-index (Musix). Electromyography of APB was performed in all patients. Results: In AIDP patients, MPS-MUNE (week-1: 85 (18-193), week-4: 87 (18-158)) and MUNIX (week-1: 113 (23-256), week-4: 124 (26-187)) differed from control MPS-MUNE (141 (66-329) and MUNIX (203 (116-364)) ( p  < 0.01, Kruskal-Wallis-rank-test). SMUP and Musix in AIDP did not differ from controls. MPS-MUNE and MUNIX did not change from week-1 to week-4. Electromyography of APB showed only slight denervation in two patients while MUP analysis was normal in all. Conclusions: Decreased MPS-MUNE and MUNIX already at week-1 in AIDP patients suggest loss of functioning axons rather than motor unit loss because of lacking denervation activity and reinnervation in most patients. Key message: MUNE methods may provide valuable information to understanding the disease pathophysiology and follow-up of AIDP.